Building Children's Character: Ethnographic Study of Maja Labo Dahu Culture at Bima Community - Umar Umar; Hendra Hendra; Mohd Hilmy Baihaqy Yussof (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
The development of the impact globalization was the emergence of manners in shifting children's characters. Therefore the aesthetic principle of Maja Labo Dahu was needed to become an instrument of development moral to build children's character. This study aimed to describe the concept of building children's character through Maja Labo Dahu, inhibiting factors, and reactualizing children’s character through Maja Labo Dahu at Bima community. This study used qualitative research with phenomenological and sociological approaches. The results showed that the exemplary aspect of parents, teachers and elite figures as the key for building children’s character. Needing implementation moral behavior through integration teaching religious and culture. The obstacle was lack of understanding of a child's culture values Maja Labo Dahu, lack of the characteristics of figures in the environment, and the absence of synergy by parents and school in establishing a children's understanding of Maja Labo Dahu. Reactualizing student’s characters involve: doing workshop and seminar to encourage strengthening of cultural character of Maja Labo Dahu and publishing Book of Muatan Lokal as literation materials in education unit level. Keywords: Maja Labo Dahu, Building Children’s Character, Strengthening of Cultural Values